Development of Front End on Tour and Travel Applications Using Python and Django Framework in PT. Industri Telekomunikasi Indonesia - Siti Nurhasanah; Muchamad Rusdan (PPM Telkom University, 2020)
The purpose of the study was to develop a website-based tour and travel application on the frontend and to make ticket reservation facilities. The research method uses a qualitative approach with data collection techniques using observation and literature study. While the system development method used is the Rational Unified Process (RUP) method. The results of the research, the development of website-based tour and travel applications on the frontend can be made with the programming language Python and Django framework and coupled with the bootstrap feature can make the frontend display on the tour and travel application more attractive. Creating a tour and travel application is expected to meet the needs of companies to improve performance in the business of PT INTI, especially in the field of information technology in the field of tour and travel services to facilitate customers to obtain information about tourist attractions, tour packages, and ticket reservations provided at tour and travel website.